The Influence of Signal Application on Mothers' Knowledge Regarding Pregnancy, Postpartum, and Newborn Emergencies in Bantul Regency - Margaretha, Sumarti Endah Purnamaningsih Maria; Rachmawati, Nur Cahya; Fijriyah, Saumi; Khasanah, Ismi Nur (Global Health Science Group, 2024)
The problem of Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Indonesia is the highest national priority that requires a focused solution. The highest MMR and IMR in DIY, namely Bantul Regency. MMR in 2022 was 16 cases, while IMR in 2022 was 90 cases, in 2023 there were 33 cases. The causes of maternal death are multifactorial, including postpartum hemorrhage, preeclampsia, sepsis, infection, and postpartum complications. In infants, common causes of death are asphyxia, transverse lie, and narrow pelvis. In addition, there is a delay in detecting and handling emergencies. And families do not yet have sufficient ability to recognize and detect high-risk pregnancies early. To make it easier for mothers to detect themselves earlier about recognizing danger signs, a technological innovation is needed that is packaged in an application that is used to identify danger signs in pregnant women, giving birth, postpartum and neonates. Type of experimental quantitative research with one group pre-test – post-test design. The design in this study did not use a control group but used a group that was given an intervention, namely Health promotion using the SIGNAL application and then given observations before and after. The population was 30 mothers who used the SIGNAL application in Bantul Regency. The sampling technique used in this study was Purposive Sampling. The type of instrument in this study was a questionnaire sheet. The research period was September to October 2024. Based on the results of the t-test analysis (paired sample t-test), it can be obtained that t count is greater than t table, which is 37.470> 1.68488 and Sig. (2 tailed) = 0.000 <0.05, then Ho is rejected and Ha is accepted. The significance result is 0.000 <0.05, then Ho is rejected and Ha is accepted, meaning that the hypothesis states that there is a difference in the results of maternal knowledge about pregnancy, postpartum and BBL emergencies before and after using the SIGNAL Application. After using the SIGNYAL application, pregnant women's knowledge about pregnancy, postpartum and newborn emergencies increased.